Antisynthetase Syndrome: A Review of Etiopathogenesis, Diagnosis and Management - E. Mirrakhimov, Aibek (Current Medicinal Chemistry, 2015)
Antisynthetase syndrome is a group of closely related rare diseases which clinically manifest with inflammatory myopathies, interstitial lung disease, inflammatory arthritis, skin hyperkeratosis (mechanic’s hands) and Raynaud phenomenon. The pathophysiology of antisynthetase syndrome is not entirely understood, but genetic predisposition, viral infections and medication use may play a role. Certain antisynthetase antibodies are associated with various clinical presentations and a lower burden of inflammatory myopathies. Patients with antisynthetase syndrome have a worse prognosis than patients with pure inflammatory myopathies mainly because of interstitial lung disease. Future research should further investigate the pathogenesis of antisynthetase syndrome which could identify new therapeutic targets. It will be also important to study whether patients with AS are at increased risk of cancer and whether certain antisynthetase antibodies have any association with the risk of malignancy.
Keywords: Antisynthetase antibodies